Right behind you [compact disc, unabridged] : a novel - Gardner, Lisa (Brilliance Audio, 2017)
Eight years ago, Sharlah May Nash's older brother beat their drunken father to death with a baseball bat in order to save both of their lives. Now thirteen years old, Sharlah has finally moved on. About to be adopted by retired FBI profiler Pierce Quincy and his partner, Rainie Conner, Sharlah loves one thing best about her new family: they are all experts on monsters.